2017
DOI: 10.1080/00380768.2017.1416670
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying rapid responses to boron deprivation in Arabidopsis roots

Abstract: Transferring hydroponically grown Arabidopsis plants (Arabidopsis thaliana L.) to boron (B)-free medium kills the cells in root tips within an hour. To understand the mechanism underlying the induced rapid cell death, the Arabidopsis response to B deprivation was characterized using inhibitors of presumably involved cellular processes. The results suggest that stretching of the plasma membrane and the influx of calcium ions through mechanosensitive channels triggered the responses and that reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 38 publications
(53 reference statements)
4
30
0
2
Order By: Relevance
“…In particular, the CrRLK FERONIA has been implicated in the perception of mechanical signals, including hypo-osmotic shock ( (Shih et al, 2014). Here we investigate the role of another class of candidate cell swelling sensors, mechanosensitive ion channels (MS) (Cazalé et al, 1998;Haswell and Verslues, 2015;Kobayashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the CrRLK FERONIA has been implicated in the perception of mechanical signals, including hypo-osmotic shock ( (Shih et al, 2014). Here we investigate the role of another class of candidate cell swelling sensors, mechanosensitive ion channels (MS) (Cazalé et al, 1998;Haswell and Verslues, 2015;Kobayashi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Boron-deficiency elevates JA levels in Arabidopsis Previous studies indicated the potential importance of JA in the low-B adaptive response in plants (Peng et al, 2012;Kobayashi et al, 2017). Short-term transcriptional analysis of the JA biosynthesis genes by quantitative reverse transcription polymerase chain reaction (qRT-PCR) showed that all were upregulated, except ACX2, ACX3, and ACX4, in response to B-deficiency treatment for 3 h in the shoots (Figure 1) and then, over the subsequent 24 h, the expression of LOX2, LOX3, AOS, AOC1, and AOC3 declined gradually (Figure 1A-C).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, B can induce molecular pathways, which correspond to a series of actions among molecules in a cell that can turn genes on and off, thereby regulating developmental phase transitions ( Figure 1 ). These transitions are involved in the coordination of the transition of plants to the adult phase ( Redondo-Nieto et al, 2012 ; Lu et al, 2014 ; Xu et al, 2016 ; Kobayashi et al, 2018 ; Sakamoto et al, 2018 ).…”
Section: The Complexity That Lies Behind the Element Boronmentioning
confidence: 99%